Challenges of Seaweed Cultivation in Nusa Penida for Economic, Tourism, and Environmental Sustainability - Putra, Ida Bagus Gede Karyambara (Bali Tourism Journal, 2023)
Seaweed production in Indonesia is distributed across 23 provinces. The top five provinces in seaweed production, according to rankings, are South Sulawesi, East Nusa Tenggara, North Kalimantan, Central Sulawesi, and West Nusa Tenggara. Among the dozens of seaweed-producing provinces, Bali has the potential for seaweed cultivation, supported by a vast marine area of 95,000 km2. The Nusa Penida sub-district of Klungkung Regency, the community shows interest in becoming seaweed farmers. The accessibility for seaweed farming in Nusa Penida is due to its location approximately ten nautical miles southeast of Bali, and its coastal area is recognized as a "museum" of rare seaweed globally. Farming activities and the seaweed production process have become a mainstay for export activities, contributing significantly to Indonesia's export value. The ease of cultivation and low capital requirements are factors that determine coastal residents' choice to become seaweed farmers. However, seaweed often faces obstacles in meeting domestic and export demands. While seaweed cultivation in Nusa Penida faces challenges, the community's resilience, coupled with innovative solutions and sustainable practices, positions seaweed as a valuable and versatile marine resource with the potential to contribute to both economic development and environmental conservation in the region.